Fine-tuning the lifetimes and energy storage capacities of meta-stable vinylheptafulvenes via substitution at the vinyl position. Issue 54 (18th May 2016) - Cacciarini, Martina; Jevric, Martyn; Elm, Jonas; Petersen, Anne U.; Mikkelsen, Kurt V.; Nielsen, Mogens Brøndsted
Abstract : A novel set of photo/thermo switches is available by one-step synthesis from the parent system. Abstract : Using a dicyano-substituted dihydroazulene (DHA) as precursor, we can access a large selection of DHAs where one cyano group has been transformed into another functionality. Upon irradiation these DHAs are readily converted into the meta-stable vinylheptafulvenes (VHFs), whose half-lives are found to span from milliseconds to days. Thus, the nature of substituent groups at the vinyl position of VHF has a strong, although not simple to predict, influence on its ability to undergo a ring-closure reaction to form a DHA.